Evaluation of case studies in European agricultural landscapes - the FEAL project - Slámová, Martina; Kruse, Alexandra; Gaillard, Bénédicte; Benedetti, Iacopo; Dreer, Johannes (JOURNAL OF LANDSCAPE ECOLOGY, 2019)
The FEAL project focused on demonstrating how multifunctional and sustainable agriculture works in practice, compiling twenty-eight case studies (CS) representing best practices. It resulted in the development of online training and educational material for young farmers. The project had ambition to collect a large variety of case studies in different European Agricultural Landscapes (EALs). The article aimed at quantitative data evaluation based on case studies to confirm the variety of EALs, natural conditions as well as the national differences in the state of landscape and nature protection. Case studies data were collected through interview campaigns (from October 2017 to March 2018) in five European countries. A contingency table was used for data processing and evaluation. The following criteria were applied for data classification from case studies: type of EAL, geomorphological characteristics (selected mesoscale landforms), land cover (CORINE Land Cover), a position of a case study inside a protected natural landscape area which pointed out to the importance of the presence of farms in protected areas. Moreover, we found out that the FEAL database of EALs, developed by the Institute for Research on European Agricultural Landscapes (EUCALAND) had to be enriched by a new EAL type. Minor consolidation of the definitions was suggested for a particular EAL.